2021
DOI: 10.1039/d0an01996h
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal spectroscopic characterization of plasmas induced by non-orthogonal laser ablation

Abstract: Plasmas induced with large ablation angles are less temporally stable and less spatially homogenous, which should be considered during quantitative analysis by laser-induced breakdown spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Studies have found that minor differences in the focusing distance can affect the spatial homogeneity of the plasma. 6,7 A change in the laser incident angle also leads to plasma asymmetry, 8 causing much larger spectral variations than that caused by laser pulse uctuations. 9 Breves et al found that spectral intensity of the emission line decreased by 28% when the incidence and collection angles changed from 0°to ±60°.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that minor differences in the focusing distance can affect the spatial homogeneity of the plasma. 6,7 A change in the laser incident angle also leads to plasma asymmetry, 8 causing much larger spectral variations than that caused by laser pulse uctuations. 9 Breves et al found that spectral intensity of the emission line decreased by 28% when the incidence and collection angles changed from 0°to ±60°.…”
Section: Introductionmentioning
confidence: 99%
“…8 As a trade-off for its instrumental robustness, LIBS exhibits a high sensitivity to changes in the analyzed target's topography 9 and matrix. 10 More importantly, LIBS is signicantly affected by the changes in experimental conditions (such as ablation 11,12 and collection geometry 13 ). A complete list of physics-related factors responsible for the structure of spectra is beyond the scope of this work and was described elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology of the sample can be characterized by surface relief and surface roughness. The variable surface relief of the sample will cause the change of LIBS system parameters, such as lens-to-sample distance (LTSD), and laser incident 10,11 and collection angles. 12 Shao J. et al 13 proved that the line intensities of copper and electron temperature rst increase and then drop with the increase of LTSD.…”
Section: Introductionmentioning
confidence: 99%